The outsider, art and humour - Clements, Paul 1959- (Routledge advances in art and visual studies, 2020)
"This cross-disciplinary book situated on the periphery of culture employs humour to better comprehend the arts, the outsider and exclusion, illuminating the ever-changing social landscape, the vagaries of taste and limits of political correctness. Each chapter deals with specific themes and approaches, from the construct of outsider and complexity of humour, to Outsider Art and spaces, using various theoretical and analytical methods. Paul Clements draws on humour especially from visual arts and culture (and to a lesser extent literature, film, music and performance) as a tool of ridicule, amongst other discourses, employed by the powerful but also as a weapon to satirize them. These ambiguous representations vary depending on context, often assimilated then re-interpreted in a game of authenticity that is poignant in a world of facsimile and 'fake news'. The humour styles of a range of artists are highlighted to reveal the fluidity and diversity of meaning which challenges expectations and at its best offers resistance and crucially a voice for the marginal. This book will be of particular interest to scholars in art history, cultural studies, fine art, humour studies and visual culture"--